The Global Regulators Lrp, LeuO, and HexA Control Secondary Metabolism in Entomopathogenic Bacteria - Engel, Yvonne; Windhorst, Carina; Lu, Xiaojun; Goodrich-Blair, Heidi; Bode, Helge B. (Frontiers in Microbiology, 2017)
Photorhabdus luminescens TTO1 and Xenorhabdus nematophila HGB081 are insect pathogenic bacteria and producers of various structurally diverse bioactive natural products. In these entomopathogenic bacteria we investigated the role of the global regulators Lrp, LeuO and HexA in the production of natural products. Lrp is a general activator of natural product biosynthesis in X. nematophila and for most compounds in TTO1. Microarray analysis confirmed these results in X. nematophila and enabled the identification of additional biosynthesis gene clusters (BGC) regulated by Lrp. Moreover, when promoters of two X. nematophila BGC were analysed, transcriptional activation by Lrp was observed. In contrast, LeuO in X. nematophila and P. luminescens has both repressing and activating features, depending on the natural product examined. Furthermore, heterologous overexpression of leuO from X. nematophila in the closely related X. szentirmaii resulted in overproduction of several natural products including novel compounds. The presented findings could be of importance for establishing a tool for overproduction of secondary metabolites and subsequent identification of novel compounds.